Conceptualising resistance to service cut-offs and household evictions : the Mandela Park Anti-eviction Campaign - Plaatjies, Isaac Hector (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2008.